2015
DOI: 10.1186/s13071-015-1207-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel combination of fipronil and permethrin (Frontline Tri-Act®/Frontect®) reduces risk of transmission of Babesia canis by Dermacentor reticulatus and of Ehrlichia canis by Rhipicephalus sanguineus ticks to dogs

Abstract: BackgroundThe ability of Frontline Tri-Act®/Frontect®, a topical ectoparasiticide containing fipronil and permethrin for dogs, to prevent the transmission of Babesia canis as well as Ehrlichia canis was evaluated by infesting dogs with infected vector ticks.MethodsFor the Babesia canis study, 16 dogs were randomly allocated to two groups. Eight dogs were treated on day 0 with a topical spot-on formulation containing 6.76 % w/v fipronil plus 50.48 % w/v permethrin and eight dogs served as the untreated control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…Importantly, it was recently shown that E. canis transmission may start a few (3-8) hours after tick attachment [95]. Tick control products such as those containing phenylpyrazoles (pyriprol, fi pronil), pyrethroids (permethrin, deltamethrin, tetramethrin, fl umethrin), amitraz and isoxazolines (fl uralaner, sarolaner, afoxolaner) have been shown to be very effective in reducing the incidence of E. canis infection and/or tick infestation, but the owners should be aware that no product can completely prevent the infection in all dogs, under all circumstances [96][97][98]. In highly endemic areas, when adequate tick control is hard to achieve, prophylactic daily use of low dose doxycycline during the tick season, reduces the risk of infection [99], although this practice may promote drug resistance.…”
Section: Preventionmentioning
confidence: 99%
“…Importantly, it was recently shown that E. canis transmission may start a few (3-8) hours after tick attachment [95]. Tick control products such as those containing phenylpyrazoles (pyriprol, fi pronil), pyrethroids (permethrin, deltamethrin, tetramethrin, fl umethrin), amitraz and isoxazolines (fl uralaner, sarolaner, afoxolaner) have been shown to be very effective in reducing the incidence of E. canis infection and/or tick infestation, but the owners should be aware that no product can completely prevent the infection in all dogs, under all circumstances [96][97][98]. In highly endemic areas, when adequate tick control is hard to achieve, prophylactic daily use of low dose doxycycline during the tick season, reduces the risk of infection [99], although this practice may promote drug resistance.…”
Section: Preventionmentioning
confidence: 99%
“…The experimental infection model used in this study was previously developed and described for the evaluation of the prevention of B. canis transmission [ 15 17 , 19 , 20 , 25 ]. The advantage of an experimental model is that the challenge load can be standardized for all dogs [ 25 ], which is not the case under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several treatments are known to kill D. reticulatus ticks and reduce B. canis transmission. In addition to the topically applied contact acaricides [ 15 17 ], systemic isoxazoline compounds have been shown to prevent B. canis transmission [ 18 20 ]. The objective of the current study was to evaluate the efficacy of a single treatment with sarolaner (Simparica®; Zoetis) at the minimum recommended label dose of 2.0 mg/kg in the prevention of B. canis transmission when dogs are challenged with infected D. reticulatus ticks 21 and 28 days after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar da permetrina possuir ação inseticida e acaricida, sua persistência não é acentuada. Sua associação ao fipronil seria desejável pois acrecentaria ação repelente e efeito "knock-down", minimizando a possibilidade que que carrapatos e pulgas consigam se alimentar e prevenindo, desta forma, a transmissão de hemoparasitos como Babesia spp., Ehrlichia canis (Jongejan et al, 2015;.…”
Section: Discussionunclassified